Seasonal Variation in Composition of Winery Wastewater in the Breede River Valley with Respect to Classical Water Quality Parameters - Howell, C.L.; Myburgh, P.A.; Lategan, E.L.; Hoffman, J.E. (South African Journal of Enology and Viticulture, 2016)
The annual wastewater quality dynamics of a winery from which wastewater was sourced for a field experiment investigating the dilution of winery wastewater for vineyard irrigation were determined. Annual mean monthly pH ranged from 4.2 to 6.8 and was lower during grape harvest than in winter. Electrical conductivity (EC) increased from the start of harvest (February) and reached a maximum in May, followed by a decline to a minimum in August. The increase in EC probably originated from cleaning agents used in the winery, as well as K+ in the grape lees and spillage from the grape fermentation process. With the exception of August, EC exceeded the critical value of 0.75 dS/m, which is the salinity threshold for water used for grapevine irrigation. The mean monthly chemical oxygen demand (COD) level increased from January and was highest at peak harvest (March). The K+ and Na+ levels in the winery wastewater increased from February to May. The sodium adsorption ratio (SAR) ranged from 2.4 to 9.0 and increased from January to June. Although COD concentration in winery wastewater is the preferred indicator of water quality for the South African wine industry, it did not provide a reliable indication of suitability for irrigation. However, EC was strongly determined by the K+ concentration. This was to be expected, since K+ is usually the most abundant cation in winery wastewater. Therefore, EC would be a more reliable indicator of winery wastewater quality than COD concentration, particularly with regard to the concentrations of cations such as K+ and Na+.